2005
DOI: 10.1016/j.gloplacha.2004.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Vivianite formation and distribution in Lake Baikal sediments

Abstract: In an effort to better understand vivianite formation processes, four Lake Baikal sediment cores spanning two to four interglacial stages in the northern, central and southern basins and under various biogeochemical environments are scrutinized. The vivianite-rich layers were detected by anomalous P-enrichments in bulk geochemistry and visually by observations on X-radiographs. The millimetric concretions of vivianite were isolated by sieving and analysed by X-ray diffraction, scanning electron microscope (SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 31 publications
4
52
1
1
Order By: Relevance
“…Nevertheless, the occurrence of Fe-oxides and -hydroxides highlight the iron mineralogy at the sediment/water interface to clearly differ from those of Lake El'gygytgyn down-core sediments deposited during glacial periods, where higher Fe concentrations are linked to the diagenetic formation of vivianite ((Fe) 3 (PO 4 ) 2 · 8 H 2 O) under reducing pore-water conditions , with manganese incorporated as an impurity into the vivianite structure (Fagel et al, 2005).…”
Section: Indicators Of Post-depositional Processesmentioning
confidence: 97%
“…Nevertheless, the occurrence of Fe-oxides and -hydroxides highlight the iron mineralogy at the sediment/water interface to clearly differ from those of Lake El'gygytgyn down-core sediments deposited during glacial periods, where higher Fe concentrations are linked to the diagenetic formation of vivianite ((Fe) 3 (PO 4 ) 2 · 8 H 2 O) under reducing pore-water conditions , with manganese incorporated as an impurity into the vivianite structure (Fagel et al, 2005).…”
Section: Indicators Of Post-depositional Processesmentioning
confidence: 97%
“…Vivianite is thought to occur at less than 1% concentration, which has made its direct identification challenging; despite this, several studies show convincing spectroscopic evidence of vivianite in lake sediments (e.g., Manning et al 1991;Fagel et al 2005;Sapota et al 2006;Rothe et al 2014). Additionally, its presence has been inferred from thermodynamic calculations (e.g., Nriagu and Dell 1974;Matisoff 1980).…”
Section: Dissolutionmentioning
confidence: 99%
“…Additionally, its presence has been inferred from thermodynamic calculations (e.g., Nriagu and Dell 1974;Matisoff 1980). Santabarbarite, altered vivianite (Pratesi et al 2003), has been shown to occur as an amorphous rim around Lake Baikal vivianite concretions (Fagel et al 2005). Ferric phosphates are sensitive to reductive dissolution both chemically and by microbial metabolism (Jones et al 1983).…”
Section: Dissolutionmentioning
confidence: 99%
“…The mineral is a regularly found deposit in sedimentary cores (e.g. Brauer et al, 1999;Fagel et al, 2005;Sapota et al, 2006;Minyuk et al, 2013). Since P is only a minor constituent in sediments, the direct identification of vivianite is difficult.…”
Section: Introductionmentioning
confidence: 99%